The Libyan crisis in the Turkish and Iranian perspectives (قضايا سياسية, 2022)
The Turkish intervention in the Libyan crisis in the recent period was a trigger for more tension than a solution - as Turkey claims - as Turkey seeks to quickly set a welcome military footing in Libya to prevent the reconciliation government from falling and planning to start exploration for gas and oil in Libya to solve the Turkish energy crisis, that is, the energy exchange for security and trying to exploit the situation to establish a new gathering of pro-Turkish political Islam, as for the Iranian position on the Libyan crisis, it does not exceed a logistical role and provide Turkey with expertise in circumventing international sanctions and assisting it in transporting fighters and weapons to Libya, Iran has also deliberately added some ambiguity to its position on the Libyan crisis and not directly interfered with it, as well as some international and regional positions regarding the Libyan crisis and Turkey's military intervention.